1998
DOI: 10.1021/jp9810724
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Isolation Fourier Transform Infrared and Ab Initio Studies of the 193-nm-Induced Photodecomposition of Formamide

Abstract: Ultraviolet irradiation of formamide in solid argon forms hydrogen-bonded, carbon- and oxygen-attached complexes NH3−CO and NH3−OC. Computationally, the carbon-attached complex is 1.2 kJ mol-1 more stable than the oxygen-attached complex. However, a thermal equilibrium of the two structures is found experimentally in the matrices. Moreover, the oxygen-attached complex dominates in the 193-nm-induced photolytic complex formation from formamide. In xenon matrices, the photochemistry of formamide increasingly yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
138
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(152 citation statements)
references
References 59 publications
14
138
0
Order By: Relevance
“…In a previous study, the ground state of the neutral molecule was studied employing the larger 6-311ϩϩG(2d,2p) basis set. 12 The results obtained in the present calculations nearly duplicate those results, and are in good agreement with the parameters as determined in experimental studies. The ground state of the radical cation derives in our calculations from the removal of an electron from the 10aЈ orbital, which is generally described as nonbonding and localized on the oxygen atom.…”
Section: A Calculationssupporting
confidence: 90%
See 1 more Smart Citation
“…In a previous study, the ground state of the neutral molecule was studied employing the larger 6-311ϩϩG(2d,2p) basis set. 12 The results obtained in the present calculations nearly duplicate those results, and are in good agreement with the parameters as determined in experimental studies. The ground state of the radical cation derives in our calculations from the removal of an electron from the 10aЈ orbital, which is generally described as nonbonding and localized on the oxygen atom.…”
Section: A Calculationssupporting
confidence: 90%
“…[7][8][9][10][11][12] These properties and the structural properties of the molecule in its electronic ground state have also been the subject of several theoretical studies. [13][14][15] Although the bond lengths and bonding angles of the ground-state structure of formamide have been well characterized in various microwave, 16 -19 gas-phase electron-diffraction, 20 and vibration-rotational studies, 21 the planarity of the molecule has for quite some time been the subject of debate, 12,22,23 in particular in relation to the possibility of a nonplanar peptide unit and in relation to the amide resonance model.…”
Section: Introductionmentioning
confidence: 99%
“…− , should be the result of a reaction between H atoms and successively NH (induced from reaction 2) and NH 2 radicals (Lundell et al 1998). The HCOṙ adical formation observed during the VUV irradiation process (band at 1850 cm −1 ) (Fig.…”
Section: Ocnmentioning
confidence: 96%
“…Furthermore, there was also the question of the photochemical stability of the amide moiety under the present experimental conditions. Lundell et al [37] reported the first photolysis experiments of formamide in both argon and xenon matrices through irradiation with an excimer laser operating at 193 nm (ArF), and observed two major channels, leading to the formation of CO and HNCO, complexed with NH 3 and H 2 , respectively. The vacuum UV photolysis (k > 160 nm) of acetamide was also studied at low temperature (in argon matrix) by Duvernay et al [38], which found HNCO:CH 4 and CO:CH 3 NH 2 molecular complexes as main products, together with acetimidic acid.…”
Section: Photochemical Experimentsmentioning
confidence: 99%